Epidemiology and strategies for chemical management of powdery mildew in mango - Pérez-Rodríguez, Amado; Monteón-Ojeda, Abraham; Mora-Aguilera, José Antonio; Hernández-Castro, Elías (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate phytosanitary strategies for the chemical control of powdery mildew (Oidium mangiferae) in mango, based on the alternation of active ingredients with different modes and sites of action, and to determine the environmental and epidemiological conditions that favor the development of the disease. The experiment was conducted in Guerrero, México, in commercial orchards, within a program for the development of fungicide spraying strategies. Epidemic curves were used on temporal analyses of the disease for: incidence; area under disease progression curve (AUDPC); severity; and conidial seasonality and its relationships with meteorological parameters. The disease was better controlled with the application of systemic fungicide followed by contact fungicide with multisite activity. The first symptoms appeared 30 days after the issuance of shoots, and the most susceptible phenological (critical) stages were at full bloom and at the onset of fruit with 8–15 mm. Optimum conditions for the development of powdery mildew, which maximizes the density of airborne spores, are temperatures higher than 30°C and relative humidity over 90%.